Alterations in the helicoverpa armigera midgut digestive physiology after ingestion of pigeon pea inducible leucine aminopeptidase - Lomate, Purushottam R.; Jadhav, Bhakti R.; Giri, Ashok P.; Hivrale, Vandana K. (Plos One, 2013)
Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on the diets supplemented with pigeon pea LAP. Aminopeptidase activities in larvae remain unaltered in presence or absence of inducible LAP in the diet. On the contrary, serine proteinase activities were significantly decreased in the larvae reared on pigeon pea LAP containing diet as compared to larvae fed on diet without LAP. Our data suggest that pigeon pea inducible LAP is responsible for the degradation of midgut serine proteinases upon ingestion. Reduction in the aminopeptidase activity with LpNA in the H. armigera larvae was compensated with an induction of aminopeptidase activity with ApNA. Our findings could be helpful to further dissect the roles of plant inducible LAPs in the direct plant defense against herbivory.